RISK MANAGEMENT OF SULAWESI MALUKU PAPUA SUBMARINE CABLE SYSTEM OF 20-1000 METER WATER DEPTH USING ANALYTICAL HIERARCHY PROCESS ABSTRACT (AHP) METHOD (CASE STUDY: PT INFRASTRUKTUR TELEKOMUNIKASI INDONESIA) - Andre Mutalibov, Mohammad
The increase in Indonesia's population is followed by the increase of active internet users in Indonesia. To fulfill the increasing demand for bandwidth, an adequate telecommunications infrastructure is needed to satisfy internet users in Indonesia. More than 99% of transoceanic data sent between islands, countries, and even continents are passed using submarine communication cables. Sulawesi Maluku Papua Cable System is one of the telecommunications infrastructures that connect the eastern side of Indonesia. Based on the company report, SMPCS Packet 2 was the submarine cable system that suffered the most damage in Indonesia. This damage disrupts the social, economic, and government sectors. This research was conducted to identify the risks that caused the damage to the cable system and providing mitigation to reduce the impact caused by these risks. The conceptual framework used in this study is Risk Management; to identify, analyze, evaluate, and mitigate risks that damage the SMPCS Packet 2 cable. Analytical Hierarchy Process is used to assist the decision-making process in choosing the best alternative for SMPCS Packet 2. Pairwise Comparison is used to conduct a quantitative assessment between criteria and alternatives. Based on the risk assessment results, it is known that the risk of Fishing & Ship Anchor is the risk that has the most significant potential in causing damage to SMPCS Packet 2. The following risk mitigation carried out is focusing on the submarine cable protection system to avoid the risk of Fishing & Ship Anchor. In determining the best submarine cable protection system, four sequential criteria must be met by each alternative, namely Reliability (51.8%) as the main criterion, Implementation (32.1%), Maintenance (9.3%), and Cost (6.9%). Determination of the best alternative is divided into three based on TelkomInfra cable laying protocol, namely 0-200 m, 200-500 m, and >500 m. The results of choosing the best alternative by the Analytical Hierarchy Process showed that the best protection system at water depth of 0-200 m uses the Burial method. For water depth of 200-500 m is using Higher Specification Cable Replacement (Double Armor/Rock Armor) and for water depth of >500 m is with High Specification Cable Replacement (Double Armor/Rock Armor).